Variability and Correlation among SST, Chlorophyll-a Levels, ENSO, and Pelagic Fishing in Southern Part of Madura Strait, Indonesia, Based on Landsat 9 OLI/TIRS Imagery - Elian, Taffy; Setiawan, Naufal (Geomatics and Environmental Engineering, 2024)
Indonesia’s marine resources are abundant, with fishing being a primary focus. The effective management of these resources requires an understanding of the factors that influence them, such as sea surface temperature (SST), El Niño-Southern Oscillation (ENSO) as indicated by the Southern Oscillation Index (SOI), and chlorophyll-a levels as food sources. This research aimed to elucidate the relationships among those factors at Madura Strait by utilizing their characteristics in response to the electromagnetic wavelengths that can be found Landsat 9 OLI/TIRS satellite images. This research utilized the satellite’s Thermal Infrared Sensor (or Band 10) (10.6–11.19 µm) to obtain the SST levels as well as the OceanColor 2 (OC2) algorithm to process Band 2 (0.45–0.51 µm) and Band 3 (0.53–0.59 µm) in order to obtain the chlorophyll-a levels. The results were the mean values of the SST (21.42 and 20.60°C) and the chlorophyll-a levels (0.77 and 0.87 mg/m3) from the periods of June through August 2022 and December 2022 through February 2023, respectively. Furthermore, a correlation test and t-test were conducted, which indicated that the chlorophyll-a levels were contradictory with the SST, SOI, and total pelagic fish catches (which were in alignment). The t-test results only indicated significant correlations between the SST and chlorophyll-a levels (–0.806) and between the SST and SOI (0.732), while the other correlation was not significant.